Oil droplet spread on an immiscible surface of a vertically falling liquid film - Zhihao Ye; Zeyu Li; Ruiting Wang; Caoxuheng Huang; Zeyu Peng (AIP Advances, 2023)
Droplet spread over a vertically falling liquid film is studied in this paper. A simulation model is built and verified by experiment. Following this, a unique phenomenon that emerges in this context, namely, a strong inertial oscillation in an early stage of spreading, is analyzed. Finally, the equilibrium features of an oil droplet in this circumstance are discussed. The results show that the maximum spreading length in a strong inertial oscillation is much longer than the equilibrium length, being 152% the length of the latter in the base case. Furthermore, the equilibrium spreading length increases nearly linearly with the initial diameter of the droplet. The paper provides data to understand the effects of an oil droplet on a vertically falling film absorber to promote energy saving in a cold storage refrigeration system with low-grade heat.